AI and Access to Justice: An Indian Perspective - Suruchi; Vikram Singh; Sanjay Dahiya (International Journal of Algorithms Design and Analysis Review, 2025)
Artificial intelligence is set to transform the legal profession, influencing everything from legal research and document review to legal advice and decision-making. This study investigates the possible uses of AI in the legal area, such as predictive analytics and AI-powered legal research tools. This study explains the role of AI in Judicial Systems. The study covers the related literature, challenges and opportunities in Indian judicial system. The usage of AI has been widely accepted in legal processes by nations namely, the United States of America, China, France, and the European Union, whereas its adoption in India is still very limited. The employment of Artificial Intelligence in the judiciary is very low and is a challenge because of the size and complexity of the Indian judicial systems. The study continues on emphasizing the importance of a responsible and ethical approach to AI adoption in the legal realm, ensuring that AI serves the interests of justice while also upholding the integrity of the legal system. The study is about the use of artificial intelligence in the field of law, and different ML and DL approaches for predicting court verdict for various type of cases. Both the pros and cons would be analysed in the context of the Indian Judicial System.
Keywords: Deep Learning; Judicial system; Machine Learning; artificial intelligence; natural language processing